2020
DOI: 10.3390/biom10030372
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Ginsenoside Components of Various Tissues of New Zealand Forest-Grown Asian Ginseng (Panax Ginseng) and American Ginseng (Panax Quinquefolium L.)

Abstract: Asian ginseng (Panax ginseng) and American ginseng (Panax quinquefolium L.) are the two most important ginseng species for their medicinal properties. Ginseng is not only popular to consume, but is also increasingly popular to cultivate. In the North Island of New Zealand, Asian ginseng and American ginseng have been grown in Taupo and Rotorua for more than 15 years. There are no publications comparing the chemical constituents between New Zealand-grown Asian ginseng (NZPG) and New Zealand-grown American ginse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 22 publications
1
39
0
Order By: Relevance
“…The main ingredients of P. quinquefolius L. are saponins, and also contain rich polysaccharides, volatile oils, and polyphenol. [3,4] In the research of polyphenols, it mainly focuses on the study of flavonoids, [5] and for the study on total polyphenols, only Wang Lijun conducts research on the polyphenol content of six saponins obtained by different elution and extraction methods from P. quinquefolium L. [6] The extraction and optimization of total polyphenols from P. quinquefolium L. have not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…The main ingredients of P. quinquefolius L. are saponins, and also contain rich polysaccharides, volatile oils, and polyphenol. [3,4] In the research of polyphenols, it mainly focuses on the study of flavonoids, [5] and for the study on total polyphenols, only Wang Lijun conducts research on the polyphenol content of six saponins obtained by different elution and extraction methods from P. quinquefolium L. [6] The extraction and optimization of total polyphenols from P. quinquefolium L. have not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous biologically active components exist in ginseng root, leaf steam and prong. These include ginsenosides ( Figure 1 ), flavonoids, triterpenoids and polysaccharides [ 12 , 13 , 14 ]. A number of studies have shown antioxidant activity of ginseng derived from both Panax quinefolium , or Panax ginseng C.A.…”
Section: Introductionmentioning
confidence: 99%
“…Some qualitative and quantitative methods have been used to evaluate the quality of PQR. In the past, scholars mostly used thin-layer chromatography to qualitatively identify PQR ( Liu Y. et al, 2016 ), or established fingerprint of PQR by high-performance liquid chromatography for the qualitative identification ( Tang et al, 2015 ).In the past, colorimetry ( Yin et al, 2010 ), near infrared spectroscopy ( Huang et al, 2011 ) nuclear magnetic resonance (NMR) spectroscopy ( Nabuurs et al, 2017 ) inductively coupled plasma method ( Jiang et al, 2020 )gas chromatography ( Lin et al, 2018 ), high performance liquid chromatography in series with various detectors ( Chen et al, 2020 , Xiong et al, 2020 ), and immunoassay ( Morinaga et al, 2010 ) were used for multi-component determination and quality control of PQR. However, there are some defects in the design of these methods.…”
Section: Physiochemical Compositionmentioning
confidence: 99%